Thermal and water ageing effect on mechanical, rheological and morphological properties of glass-fibre-reinforced poly(oxymethylene) composite - Kuram, Emel (Sage Publications Ltd, 2019)
In this study, the ageing behaviour of glass-fibre-reinforced poly(oxymethylene) composite at different conditions was investigated. The ageing was performed in various controlled environments, namely in air at room temperature, in water at room temperature and in an oven at the temperature of 100 celcius. Tensile and flexural tests were conducted to determine the mechanical properties, melt flow index was measured to determine the rheological property and scanning electron microscopy was used to observe the morphological property of unaged and aged poly(oxymethylene) samples. A reduction in both tensile and flexural strength was observed with all ageing environment. The worst strength retention was obtained with water ageing. Water absorbed by glass-fibre-reinforced poly(oxymethylene) composite had a detrimental influence on the tensile and flexural strength. Tensile strength was affected by the ageing environments. The decrease in the tensile strength of air and thermally aged poly(oxymethylene) was slower than that of water aged poly(oxymethylene), and the tensile strength of aged samples decreased as the ageing time increased. The combined actions of heat, air and water (thermal + water + air ageing) did not further degrade glass-fibre-reinforced poly(oxymethylene) compared to only water ageing at the room temperature. All tensile stress-strain and flexural load-deflection curves showed the similar tendency and did not change with ageing environments and time. All aged samples showed higher melt flow index values than that of unaged sample and the changes in melt flow index could be an indicator of degradation.
Keywords: Ageing; composite; degradation; mechanical properties; injection molding